Aktivitas Antibakteri Ekstrak Etanol Daun Bandotan (Ageratum Conyzoides L.) Terhadap Bakteri Streptococcus Pyogenes - Jovita Almira; Yusransyah Yusransyah; Banu Kuncoro; Rahmawida Putri; Nuriyatul Fhatonah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The treatment of bacterial infectious diseases using a semi synthetic antibiotic can lead to resistance, so that the search is necessary to overcome it the ingredients of natural medicine from plants, one of them namely bandotan leaf extract (Ageratum conyzoides l.). This research aims to identify the chemical compounds contained in leaf bandotan and knowing his activity as antibacterial against Pseudomonas aeruginosa and s. pyogenes. The leaves are extracted in bandotan maceration using solvent ethanol 96%. The extract was tested using the method of antibacterial activity of sumuran and clear zones are measured that is formed using a caliper and triplo. The results of the identification of a compound leaf bandotan secondary metabolite showed a group of compounds alkaloids, saponins, tannins, flavonoids, phenolic, triterpenoid glycosides, steroids,. Based on a test of antibacterial activity against s. pyogenes with the concentration of 100%, 50%, 25%, 12.5%, 6.25% showed a clear zone on the concentration in a row with an average of 14.52 mm; 13.87 mm; 13.38 mm; 12.38 mm; 11.75 mm; 15.33 mm. While testing the antibacterial activity against Pseudomonas aeruginosa with the same concentrations did not show the presence of antibacterial activity of extracts of leaves of bandotan with no clear zone formation